Ulnar articular surface 3-D landmarks and ecomorphology of small mammals : a case study of two early Miocene typotheres (Notoungulata) from Patagonia - Muñoz, Nahuel A. (2017)
Fil: Muñoz, Nahuel A.. División Paleontología Vertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina